Supporting Health-Care Workers and Patients in Quarantine Wards: Evidence From a Survey of Frontline Health-Care Workers and Inpatients With COVID-19 in Wuhan, China - Zhou, Ting; Guan, Ruiyuan; Rosenthal, Susan L.; Moerdler, Scott; Guan, Ziqi; Sun, Liqun (Frontiers in Public Health, 2021)
Objective: Frontline healthcare workers and patients with COVID-19 have been identified as high-risk groups for psychological problems. Experience of working or staying in quarantine wards generated psychological stressors for healthcare workers and patients with COVID-19. The present study aimed to investigate psychological symptoms of hospitalized patients with COVID-19 and the healthcare workers treating them during the outbreak period, examine the effects of psychological stressors on mental health in both population and perceived coping resources for both sides. Methods: Three hundred and eleven healthcare workers working in a COVID-19 designated hospital in Wuhan, China, and 148 hospitalized patients with COVID-19 in the same hospital participated in this cross-sectional survey conducted in February 2020. Psychological symptoms, psychological stressors, and perceived coping resources were reported by both groups. Results: Thirty-three percent of healthcare workers and 35.2% of patients with COVID-19 had significant psychological symptoms which were indicative of high risk for psychological disorders. Concern about patients was one aspect of psychological stressors of frontline healthcare workers and both groups perceived support from the opposite side as an important external coping resource. Conclusion: The results shed light on the need to provide psychological support to both frontline healthcare workers and patients with COVID-19 and suggest enhancing the treatment alliance might be effective to improve mental health for both populations during the crisis.